Pete the cat - Old MacDonald had a farm - Dean, James 1957- (Harper / HarperCollins, 2014)
"Pete the cat learns the sounds of the different farm animals in this twist on the classic song"..
Keywords: Folk songs, English -- United States -- Texts; Animal sounds; Domestic animals; Cats; Folk songs; USA